Correlation Analyses of Clinical Manifestations and Variant Effects in KCNB1-Related Neurodevelopmental Disorder - Xiong, Juan; Liu, Zhonghua; Chen, Shimeng; Kessi, Miriam; Chen, Baiyu; Duan, Haolin; Deng, Xiaolu; Yang, Lifen; Peng, Jing; Yin, Fei (Frontiers in Pediatrics, 2022)
Objective:Vitro functional analyses of KCNB1 variants have been done to disclose possible pathogenic mechanisms in KCNB1-related neurodevelopmental disorder. “Complete or partial loss of function (LoF),” “dominant-negative (DN) effect” are applied to describe KCNB1 variant's molecular phenotypes. The study here aimed to investigate clinical presentations and variant effects associations in the disorder. Methods: We reported 10 Chinese pediatric patients with KCNB1-related neurodevelopmental disorder here. Functional experiments on newly reported variants, including electrophysiology and protein expression, were performed in vitro. Phenotypic, functional, and genetic data in the cohort and published literature were collected. According to their variants' molecular phenotypes, patients were grouped into complete or partial LoF, and DN effect or non-dominant-negative (non-DN) effect to compare their clinical features. Results: Nine causative KCNB1 variants in 10 patients were identified in the cohort, including eight novel and one reported. Epilepsy (9/10), global developmental delay (10/10), and behavior issues (7/10) were common clinical features in our patients. Functional analyses of 8 novel variants indicated three partial and five complete LoF variants, five DN and three non-DN effect variants. Patient 1 in our series with truncated variants, whose functional results supported haploinsufficiency, had the best prognosis. Cases in complete LoF group had earlier seizure onset age (64.3 vs. 16.7%, p = 0.01) and worse seizure outcomes (18.8 vs. 66.7%, p = 0.03), and patients in DN effect subgroup had multiple seizure types compared to those in non-DN effect subgroup (65.5 vs. 30.8%, p = 0.039). Conclusion: Patients with KCNB1 variants in the Asian cohort have similar clinical manifestations to those of other races. Truncated KCNB1 variants exhibiting with haploinsufficiency molecular phenotype are linked to milder phenotypes. Individuals with complete LoF and DN effect KCNB1 variants have more severe seizure attacks than the other two subgroups.